Проблеми відтворення наукових кадрів старопромислових регіонів Донбасу і Придніпров’я для забезпечення їх інноваційної модернізації - Іванов, С.В.; Антонюк, В.П.; Ляшенко, В.І. (Економічний вісник Донбасу, 2020)
У статті здійснено аналіз стану і динаміки наукових кадрів старопромислових регіонів України. Виявлено негативні тенденції: скорочення зайнятих у сфері наукових досліджень та розробок, зменшення чисельності дослідників; погіршення якісного складу кадрового потенціалу науки, що проявилося у зниженні част¬ки дослідників з науковими ступенями та науковців більш молодого віку; зменшення обсягів підготовки наукових кадрів в аспірантурі. Це перешкоджає інноваційній модернізації регіональних економік. Особливо негативні процеси у сфері кадрового забезпечення науки відбулися в Донецькій і Луганській областях внаслідок окупації частини території та подальшого занепаду їх економік, частка виконавців НДР в цих регіонах складає відповідно 0,03 та 0,1% від усіх зайнятих. Основними причинами втрати кадрового потенціалу науки старопромислових регіонів є технологічна відсталість їх економік та надзвичайно низький рівень фінансування науково-дослідної сфери. Зроблено висновок про необхідність комплексної модернізації соціально-економічного комплексу старопромислових регіонів, яка має базуватися на взаємопов’язаній реіндустріалізації і смартспеціалізації регіональних економік та відродженні науково-дослідного сектору. В статье представлен анализ динамики научных кадров старопромышленных регионов Украины. Систематизированы негативные тенденции, такие как: сокращение занятых в научно-исследовательской сфере, уменьшение численности исследователей; ухудшение качественного состава кадрового потенциала науки, что выразилось в уменьшении удельного веса исследователей с научными степенями и ученых более молодого возраста; уменьшение объёмов подготовки научных кадров в аспирантуре. Это препятствует инновационной модернизации региональных экономических комплексов. Наиболее негативные процессы в сфере кадрового обеспечения науки произошли в Донецкой и Луганской областях вследствие потери части оккупированной территории и продолжающегося падения их экономик, удельный вес исполнителей НИР в этих регионах составляет соответственно 0,03 та 0,1% всего занятого населения. Основные причины потери кадрового потенциала науки старопромышленных регионов кроются в технологической отсталости их экономик и критически низком уровне финансирования научно-исследовательской сферы. Сделан вывод о необходимости комплексной модернизации социально-экономического комплекса старопромышленных регионов, которая должна базироваться на взаимоувязанной реиндустриализации и смартспециализации региональных экономик и возрождении научно-исследовательского сектора. The state and dynamics of quantitative and qualitative parameters of research personnel in the old industrial regions of Ukraine – Dnepropetrovsk, Donetsk, Zaporozhye, and Lugansk regions have been analyzed. Negative trends have been identified in all regions: a reduction in employment in research and development, a decrease in the number of researchers; the deterioration in the qualitative composition of human capacity in science which has been reflected in a decrease in the share of researchers with scientific degrees and scientists of a younger age; reducing the volume of training of research personnel in graduate school. The loss of human capacity in science hinders the innovative modernization of regional economies. Particularly negative processes in the field of staffing science occurred in the Donetsk and Lugansk regions as a result of the occupation of part of the territory, the movement of some research institutions to other regions and the further decline of their economies. The share of R&D performers in these regions is respectively 0.03% and 0.1% of all employees. It has been concluded that in the regions of Donbass there are practically no internal sources of scientific and technological development currently. The main causes of the loss of human resources capacity of science of the old industrial regions are technological backwardness of their economies, stagnation of innovation and extremely low level of financing scientific research. The conclusion has been drawn on the need for a comprehensive modernization of the socio-economic complex of the old industrial regions, which should be based on interconnected processes of reindustrialization and smart specialization of regional economies and the revival of the research. These require the identification of promising high-tech types of economic activity in the regions and those branches of scientific research that will ensure their support.